2020
DOI: 10.3390/toxins12020116
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Lysosomes Participate in Vip3Aa-Induced Spodoptera frugiperda Sf9 Cell Apoptosis

Abstract: Vip3Aa, a soluble protein produced by certain Bacillus thuringiensis strains, is capable of inducing apoptosis in Sf9 cells. However, the apoptosis mechanism triggered by Vip3Aa is unclear. In this study, we found that Vip3Aa induces mitochondrial dysfunction, as evidenced by signs of collapse of mitochondrial membrane potential, accumulation of reactive oxygen species, release of cytochrome c, and caspase-9 and -3 activation. Meanwhile, our results indicated that Vip3Aa reduces the ability of lysosomes in Sf9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…Another study has evidenced the involvement of regulatory proteins and lysosomes in apoptosis. Furthermore, symptoms of apoptosis and mitochondrial collapse are prevalent in sf9 cells when administered Vip3Aa, such as the accumulation of reactive oxygen species (ROS), caspases (caspase 3,9), and cytochrome c [66] ( Figure 3). Because of the lack of sound information, more investigation is needed to clarify the downstream mechanism of Vip3 induced apoptosis and cell death.…”
Section: Mechanism Of Action Of Vip3 Toxinmentioning
confidence: 99%
“…Another study has evidenced the involvement of regulatory proteins and lysosomes in apoptosis. Furthermore, symptoms of apoptosis and mitochondrial collapse are prevalent in sf9 cells when administered Vip3Aa, such as the accumulation of reactive oxygen species (ROS), caspases (caspase 3,9), and cytochrome c [66] ( Figure 3). Because of the lack of sound information, more investigation is needed to clarify the downstream mechanism of Vip3 induced apoptosis and cell death.…”
Section: Mechanism Of Action Of Vip3 Toxinmentioning
confidence: 99%
“…Recently, efforts have been made to dissect the mitochondrial-mediated pathway of apoptotic cell death, which has revealed the importance of lysosomes in this process ( Hou et al, 2020 ). The toxin induces the build-up of reactive oxygen species, cytochrome release, disruption of mitochondrial membrane potential, and activation of caspases (3 and 9) resulting in morphological changes (swelling and distorted cristae); overall dysfunctioning of mitochondria and finally reduced the viability of Sf9 cells.…”
Section: Vegetative Insecticidal Proteins (Vips)mentioning
confidence: 99%
“…Since their discovery in 1996 [24], Vip3A proteins have been the subject of intensive research. It has been reported that Vip3A stimulates membrane pore formation and apoptosis upon binding to target cells, which is proposed to be responsible for its cytotoxic effects [12,[25][26][27]. The scavenger receptor class C like protein (Sf-SR-C) and the fibroblast growth factor receptor (Fgfr) have been reported as potential receptors for Vip3A [10,11].…”
Section: Introductionmentioning
confidence: 99%